The morality of nationalism - McKim, Robert; McMahan, Jeff (Oxford University Press on-line., 1997)
Nationalism is one of the most serious political problems in the world today. This volume is a collection of papers which address the topic of the ethics of nationalism. The contributors include some of the most eminent political philosophers and political scientists active today. The bulk of the literature on nationalism is in the social sciences and tends to focus on descriptive and prescriptive themes and issues of policy. This collection, however, focuses on the deeper moral issues that must be addressed if a policy prescription is to be well grounded.